Moist exposed burn ointment for treating pressure ulcers: A multicenter randomized controlled trial. Issue 29 (July 2017) - Li, Wei; Ma, Yubo; Yang, Qi; Pan, Yu; Meng, Qinggang
Abstract: Background: Pressure ulcers often seriously affect the quality of life of patients. Moist Exposed Burn Ointment (MEBO) has been developed to treat patients with pressure ulcers. The present study aimed to evaluate the efficacy and safety of MEBO in the treatment of pressure ulcers in Chinese patients. Methods: Seventy-two patients with pressure ulcers were randomly assigned to 2 groups who received a placebo or MEBO for 2 months. The primary outcomes included the wound surface area (WSA) and pressure ulcer scale for healing (PUSH) tool. The secondary outcomes included a visual analog scale (VAS), questionnaire of ulcer status, and adverse effects. Results: Sixty-seven patients completed the study. After 2 months of treatment, the difference of mean change from the baseline was greater for MEBO (vs placebo) for WSA mean (SD) −6.0 (−8.8, −3.3), PUSH Tool −2.6 (−4.7, −1.5), and VAS score −2.9 (−4.4, −1.7). On the basis of the questionnaire, the pressure ulcers were "completely healed" (50.0% vs 16.7%) ( P  < .05) in patients after 2 months of treatment with MEBO versus placebo. No major adverse effects were found in the 2 groups. Conclusion: We showed that MEBO is effective and well tolerated for improving wound healing in Chinese patients with pressure ulcers.